BID'AH IN HIGHLIGHTS OF FIQH - Musawar Musawar (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2019)
This paper seeks to analyze the term "Bid'ah" which at this time is always used as a basis for justifying an act, whether the act appears good, whether it is included in customary culture, and so on. Therefore, social divisions often occur which have a negative impact in the midst of community life. Even because of the importance of this discussion, some scholars' included it in theological issues (aqidah). This means that knowledge about heresy is in line with the problem of faith that must be known by someone and this results in many people blaming each other, even people who disbelieve each other when someone does an act of "heresy". Therefore, knowing which actions and when are called "heresies" becomes important so that one will be careful in doing an act, because a person who commits heresy, then he has tried to oppose Shari'a. However, an important thing to note is understanding comprehensively about the concept of bid'ah, so that people are not trapped in the concept because if a person is trapped he becomes supported in it. This will result in a tight shari'ah. Instead, people feel free and separated from the concept of heresy, then they have ignored the signs of the heresy concept itself. From this, a complete understanding of bid'ah becomes urgency. The author tries to write it with a library research approach by collecting data related to the term "bid'ah".